DIFFERENT INTERPRETATION OF AMBIGUITIES SENTENCES (A Study of Class C the Second Semester Postgraduate Students Majoring English of State University of Semarang) - Humaira Humaira (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2015)
Ambiguityis strictly speaking, used to describe aword, phrase, or sentence when it has more thanone interpretation.Sometimes we found many ambiguities sentences when we are reading or listen to the English sentences. Multiinterpretations not only happen from the English language learners, but also in native speakers themselves. Thisstudy investigated about is there any different interpretation of ambiguities sentences made by students of class c,second semester students of PPs Unnes?, and what types of ambiguous sentence majority missing in theirtranslating. The objectives of study were to know that the students of PPs Unnes have different interpretations whenthey are translating the ambiguities sentences and to identifying the types of ambiguities. This study used descriptivequalitative approach; ten postgraduate students from Class C PPs Unnes participated in this study as respondents.All were university students majoring in English. They were given 5 ambiguous sentences. Sentences includedifferent sources of ambiguity such as, structural ambiguity, and lexical ambiguity. The subjects were asked totranslate the sentences into Indonesian language. The result of study presented that participants who are not nativespeakers of English exhibited the different interpretations in translate both the given types of ambiguous sentences.Almost all of ten respondents have different interpretations in each ambiguous sentence. Most respondents showdifferent translating majority in lexical ambiguous sentences.